2014
DOI: 10.3892/mco.2014.419
|View full text |Cite
|
Sign up to set email alerts
|

Association of CA 15-3 and CEA with clinicopathological parameters in patients with metastatic breast cancer

Abstract: Abstract. The objective of this study was to investigate the association of serum cancer antigen and carcinoembryonic antigen (CEA) levels with clinicopathological parameters in patients diagnosed with metastatic breast cancer (MBC). We retrospectively evaluated the medical records of 284 patients diagnosed with MBC between January, 2007 and December, 2012 who fulfilled the specified criteria and the association between the levels of the two tumor marker and clinicopathological parameters was analyzed. Of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
3
12

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 22 publications
1
35
3
12
Order By: Relevance
“…In agreement with Fang's results, they found that CEA and CA153 did not correlate with molecular subtypes, but they found that CA125 exhibited statistical differences among various molecular subtypes, with the most frequent elevations occurring in the triple-negative tumors. 7 As for metastatic breast cancer, Geng et al 16 concluded that elevated CA 153 and CEA levels at initial diagnosis of recurrence were found to be associated with breast cancer molecular subtypes. In addition, Wu 6 and his colleagues reported that CEA levels were lower in patients with triple-negative breast cancer than patients with other subtypes, and CA153 did not correlate with molecular subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with Fang's results, they found that CEA and CA153 did not correlate with molecular subtypes, but they found that CA125 exhibited statistical differences among various molecular subtypes, with the most frequent elevations occurring in the triple-negative tumors. 7 As for metastatic breast cancer, Geng et al 16 concluded that elevated CA 153 and CEA levels at initial diagnosis of recurrence were found to be associated with breast cancer molecular subtypes. In addition, Wu 6 and his colleagues reported that CEA levels were lower in patients with triple-negative breast cancer than patients with other subtypes, and CA153 did not correlate with molecular subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor markers have been widely used for assessment of treatment responses, early diagnosis of recurrence and prognosis. In breast cancer, the most generally used serum tumor marker is cancer antigen 15-3 (CA 15-3); however, its sensitivity and specificity are inadequate (2,3). Numerous serum markers have been studied, however, none have been implemented for routine clinical practice (4).…”
Section: Introductionmentioning
confidence: 99%
“…The united measurement of both serum markers permits early diagnosis of metastases in up to 60-80% of breast cancer patients [19]. Recent study shows that elevated CA 15-3 and CEA levels were identified in 163 (57.4%) and 97 (34.2%), respectively, of the 284 patients with distant metastasis [20]. Thus, we studied the role of both Trx-1 and MMP-9 in diagnosis of breast cancer and their correlation with clinicopathological parameters of MBC and NMBC Egyptian patients, as well as, their sensitivity and specificity in the disease prognosis.…”
Section: Discussionmentioning
confidence: 99%